2014
DOI: 10.1186/preaccept-2592972001406136
|View full text |Cite
|
Sign up to set email alerts
|

Updated canine infection rates for Dirofilaria immitis in areas of Brazil previously identified as having a high incidence of heartworm-infected dogs

Abstract: Background: Canine heartworm infections were frequently diagnosed in Brazil before the new millennium. After the year 2000, the frequency of diagnosis showed a sharp decline; however, a few years later, new evidence indicated that the parasite was still present and that canine infection rates seemed to be increasing. Therefore, an updated survey of canine heartworm prevalence was conducted in several locations in south, southeast, and northeast Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…Our findings are in close association with Labarthe et al . [20] who found that younger dogs (1-2 year) were less likely to be detected positive than dogs of older age groups. Long prepatent period (6-7 months) needed to complete the life cycle of filarial worms in dogs was also proposed as the reason for the same.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in close association with Labarthe et al . [20] who found that younger dogs (1-2 year) were less likely to be detected positive than dogs of older age groups. Long prepatent period (6-7 months) needed to complete the life cycle of filarial worms in dogs was also proposed as the reason for the same.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the unavailability of melarsomine-based products in Brazil and taking into consideration the increased prevalence of heartworm infection in the country [ 23 , 24 ], the aim of the present study was to evaluate the efficacy of a heartworm-preventive protocol that includes the commercial formulation of an extended-release injectable moxidectin suspension (ProHeart ® SR-12) administered every six months plus cycles of 30-day treatment with oral doxycycline in dogs naturally infected with D. immitis.…”
Section: Introductionmentioning
confidence: 99%
“…Aedes aegypti is the vector of several viruses, most notably dengue, yellow fever, chikungunya, Zika and the filarial roundworm Wuchereria bancrofti which causes lymphatic filariasis [ 4 ]. Culex quinquefasciatus transmits the heartworm Dirofilaria immitis , causing microfilariasis in some coastal cities [ 5 ] and is incriminated in the transmission of several viruses such as Saint Louis encephalitis virus, Mayaro virus, eastern equine encephalitis virus and Rocio viral encephalitis virus [ 3 ]. Culex spp.…”
Section: Introductionmentioning
confidence: 99%